2021
DOI: 10.1021/acsomega.1c04430
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification Effect of Compound Solutions of Surfactants with Acetic Acid on Coal Pores

Abstract: Coal seam pores are the major places for coalbed methane storage, diffusion, and seepage, and changes in the pore structure cause changes in the porosity. The porosity of coal seams can be effectively improved by applying strongly corrosive and oxidative chemical reagents to coal seam pores, but these reagents may pose threats to coal workers, corrode mining equipment, and pollute the environment. In this study, coal samples were treated with solutions compounded by acetic acid and anionic, cationic, and non-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Therefore, welldeveloped pore and fracture network is essential for the fast and efficient gas extraction (Liu et al, 2023). However, for coal seams with high mineral content, the pores and fractures are often blocked by minerals (such as calcite, kaolinite and pyrite), which seriously hampers the desorption and migration of CBM (Chen S. et al, 2021). Aiming at this problem, many studies have demonstrated that acidizing treatment can effectively remove the minerals and link the blocked channels (Turner and Steel, 2016;Wang et al, 2020;Chen Q. et al, 2021;Guo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, welldeveloped pore and fracture network is essential for the fast and efficient gas extraction (Liu et al, 2023). However, for coal seams with high mineral content, the pores and fractures are often blocked by minerals (such as calcite, kaolinite and pyrite), which seriously hampers the desorption and migration of CBM (Chen S. et al, 2021). Aiming at this problem, many studies have demonstrated that acidizing treatment can effectively remove the minerals and link the blocked channels (Turner and Steel, 2016;Wang et al, 2020;Chen Q. et al, 2021;Guo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many scholars have performed studies on the variation of coal pore structure under acidification. In these studies, the pore structure was commonly characterized by nuclear magnetic resonance (NMR), scanning electron microscopy (SEM), gas adsorption method (GA), and highpressure Mercury intrusion (MIP) (Zhang et al, 2016;Zhao et al, 2018;Ni et al, 2020;Wang et al, 2020;Liu et al, 2021;Xie et al, 2021;Yi et al, 2021). For example, Ni et al explored the changes in pore structure under nitric acid treatment by SEM and LTGA-N 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, many scholars are using different surfactants to change the wettability of the coal surface, which in turn affects the pore structure and adsorption properties of coal. Meng et al and Liu et al formed an effective directional closely aligned adsorption layer after surfactant treatment of lignite, which facilitates coal adsorption. Ma et al concluded that SPAN80 can change the wettability of the coal surface and attenuate the effect of oxygen-containing functional groups on the coal surface through hydrogen bonding adsorption by the surfactant SPAN80 on the promotion of coal slurry flotation.…”
Section: Introductionmentioning
confidence: 99%